STRATEGI PENGURUS YAYASAN BONAVIDA SINGGEURA MILIR INDRAMAYU DALAM MENGELOLA ZAKAT, INFAQ DAN SHODAQOH (ZIS) - Asrof Fitri, Ahmad; Sobirin; Santoso, Budi (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Zakat has a big role in poverty alleviation efforts. For that we need good management and management. One of the non-governmental institutions that have the authority to manage zakat is the foundation. The foundation where the researcher conducted the research is called the Bonavida Singgeura Milir Indramayu Foundation (YBSMI). The author's goal of conducting research at this foundation is to find out the management's strategy in managing zakat, infaq and shodaqoh (ZIS), including what are the supporting factors and inhibiting factors faced by the foundation's management. To answer these questions, researchers used qualitative research methods with a descriptive approach. Data collection techniques that researchers use are interviews, observation and documentation. After conducting research, the authors found that the strategy used by the foundation's management in managing ZIS was by conducting outreach from house to house or from mosque to mosque. In addition, the management also utilizes social media as a means of socializing various foundation activities. As for the supporting factors, in addition to the cohesiveness of all the management, there is also support from the management's family such as his wife and even his children, plus the support from the residents and the closest government agencies. While the inhibiting factors include the lack of public awareness to set aside part of their wealth for orphans.